Complexes of Cobalt(II), Nickel(II) and Copper(II) with an Ambivalent Schiff Base Ligand - Rai, H.C.; Singh, A.S.; Mishra, Amrita; Kumar, Rajiv; Chaudhary, S.P. (Asian Journal of Chemistry, 2010)
Condensation of 1-phenyl-1,2-proparndione-2-oxime with 1,2-diaminobenzene in an ethanolic medium yields a Schiff base ligand, bis-(1-phenyl-2-hydroxyimino-1-propylidene) 1,2-diaminobenzene, H2L. A number of complexes of the types [ML] [M = Co(II), Ni(II), Cu(II}], [M(H2L)X2] [M = Co(II), Ni(II), X = Cl–, Br–, I–, ClO–4, NO–3] and [Cu2LX2] [X = Cl–, Br–, I–, ClO–4, NO–3] have been synthesized and characterized on the basis of their elemental analyses, magnetic moment, infrared and electronic spectral data as well as conductivity measurements where the ligand behaves as a tetradentate ligand in the first two series and in a hexadentate manner in the third one.